PENERAPAN MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN BERPIKIR KRITIS SISWA PADA MATERI SISTEM PENCERNAAN MANUSIA - Rizka Syafitri Adhitya; An Nuril Maulida Fauziah (PENSA: E-JURNAL PENDIDIKAN SAINS, 2023)
This research aimed to determine the problem based learning implementation model toward students' critical thinking skills on the material of human digestive system. This research used pre-experimental design with one group pretest posttest. The subjects’ in this research were 30 students’ of VIII C class in Junior High School Semen Gresik with 20 male students’ and 10 female students’. Data collection technique used questionnaires, pretest and posttest. The data was analyzed quantitatively. The results of the N-Gain calculation showed that the application of problem based learning model increased students' critical thinking skills on the human digestive system material with a high category. Descriptive analysis on learning activities by the given treatment had a high percentage result. The conclusion obtained was science learning using a problem based learning model on the human digestive system material can improve students’ critical thinking skills.